(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
Jointed goatgrass (Aegilops cylindrica Host; 2n = 4x = 28, CcCcDcDc) is a tetraploid remote relative of bread wheat (Triticum aestivum L; 2n=6x=42, AABBDD) with two genomes and 28 chromosomes. The diversity center of this species is in the Fertile Crescent and in central Asia and could also be found in many places in Iran. In this experiment, 359 accessions provided by National Plant Gene Bank of Iran (NPGBI) were used. Based on the geographical distribution, the highest distribution of A. cylindrica is found in North, West and North-West regions of Iran. The data on the distribution of A. cylindrica showed that its distribution centers in Iran are more than those reported in the previous studies. Chromosome counting showed that all A. cylindrica accessions are tetraploid (2n=4x=28). Results of factor analysis for nine morphological chromosome traits showed that karyotypic variation within accessions are related to the length of chromosomes and there is difference between the accessions for their total chromosome length, but the karyotype of different accessions are almost the same for the symmetry. Low coefficient of variation in morphological traits as well as symmetric karyotypes of A. cylindrica species observed in this study could lead us to predict that A. cylindrica could be a recently evolved species among the remote relatives of bread wheat.